Transition Rates from Benign Paroxysmal Positional Vertigo to Persistent Postural-Perceptual Dizziness - Masaki, Yoshio (International Journal of Practical Otolaryngology, 2023)
Persistent postural-perceptual dizziness (PPPD) is a chronic dizziness disorder that is newly listed in the World Health Organization (WHO)'s International Classification of Diseases (ICD-11) revised in 2018. In this study, I selected definite cases of the first occurrence of benign paroxysmal positional vertigo (BPPV) among vertigo patients who visited our clinic in the past 1 year, and retrospectively reviewed the age at the first visit, gender, affected side, previous medical conditions, type of BPPV, and their tendency toward transition to PPPD. Eligible patients were new first-ever cases of BPPV who visited our clinic during the 1-year period from June 1, 2020, to May 31, 2021, and who met the diagnostic criteria for BPPV established by the Japan Society for Equilibrium Research. There were 311 cases, including 120 men and 191 women, with a male:female ratio of 1:1.6; hence, the majority of patients were women. The mean age ± standard deviation was 60.7 ± 17.8 years. Men ranged in age from 14 to 88 years, with a mean age of 64.2 ± 16.3 years. Women ranged in age from 11 to 90 years, with a mean age of 58.5 ± 18.5 years. Thus, the average age of the men was higher. As for the type of BPPV, there were 172 cases of posterior semicircular canal-type BPPV (canalolithiasis), 79 cases of lateral semicircular canal-type BPPV (canalolithiasis), and 60 cases of lateral semicircular canal-type BPPV (cupulolithiasis), with the posterior semicircular canal-type BPPV (canalolithiasis) being the most common. In regard to the affected side, the right side was affected in 164 cases and the left side in 147 cases; thus, involvement of the right side was more common. The time to remission was less than 0.5 months in 86 cases, less than 1 month in 69 cases, less than 2 months in 50 cases, less than 3 months in 22 cases, and more than 3 months in 57 cases. Remission was achieved in less than 3 months in 72.9% of cases. The course remained unknown in 27 cases, as the patients discontinued their clinic visits. There was only one case of a 75-year-old man and one case of a 70-year-old woman who transitioned to PPPD. Both cases had left-sided posterior semicircular canal-type BPPV (canalolithiasis). The man had underlying hypertension, while the woman had underlying hypertension and diabetes mellitus. The rate of transition from BPPV to PPPD was 0.6% when cases with an unknown course were included, and the rate was as low as 0.7% when cases with an unknown course were excluded. Thus, the frequency of transition from BPPV to PPPD is low.
Keywords: persistent postural-perceptual dizziness; benign paroxysmal positional vertigo; dizziness